Strut formation control and processing time optimization for wire arc additive manufacturing of lattice structures. (July 2022) - Yu, Ziping; Pan, Zengxi; Ding, Donghong; Rong, Zixuan; Li, Huijun; Wu, Bintao
Abstract: Lightweight aluminum alloy lattice structures have broad application prospects in energy absorption, heat insulation, vibration isolation, etc. Additive manufacturing (AM) has been increasingly applied to fabricating lattice structures due to its efficient and flexible technical characteristics. Wire arc additive manufacturing (WAAM), featuring high productivity and low cost, is gradually considered a desirable choice for rapid prototyping of medium to large-scale freeform metallic lattice structures. However, due to the higher thermal conductivity of aluminum alloys, the forming of struts is more easily affected by the interlayer temperature. The control and prediction of strut formation during the fabricating process is the challenge facing the current industry. Simultaneously, there is also an urgent need to improve its processing efficiency. Therefore, this paper describes the strut-based finite element model for numerical simulation of the WAAM thermal process of the ER 4043 aluminum alloy lattice structure. The FE model is calibrated and validated through temperature measurements with thermocouples and a thermal imager. The calibrated FE model was employed to simulate the manufacturing process of the lattice structure. A novel fabrication sequence planning strategy was proposed to make the interlayer temperature distribution uniform so as to optimize the processing time while ensuring stable strut formation. Graphical abstract: Unlabelled Image